2013
DOI: 10.1007/s11077-013-9174-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulatory spaces

Abstract: This article develops the concept of ‘‘Functional Regulatory Space’’ (FRS) in order to analyze the new forms of State action addressing (super) wicked problems. A FRS simultaneously spans several policy sectors, institutional territories and levels of government. It suggests integrating previous policy theories that focused on ‘‘boundary-spanning regime,’’ ‘‘territorial institutionalism’’ or multi-level governance. The FRS concept is envisaged as a Weberian ‘‘ideal-type’’ of State action and is applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 49 publications
0
40
0
6
Order By: Relevance
“…Regarding the first, although the current policy integration body of literature primarily focuses on horizontal integration between domains or services (Tosun and Lang 2013), similar integration challenges arise in multi-level governance contexts (Briassoulis 2011). A promising way of expanding the framework in this respect is by linking it to the notion of 'functional regulatory spaces,' which span several policy sectors, governance levels, and institutional territories (Varone et al 2013). Regarding the integration of policy outcomes, as Jordan and Lenschow (2010) observe, relatively little research has been conducted on the effects of better integrated policy approaches on actual practices on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first, although the current policy integration body of literature primarily focuses on horizontal integration between domains or services (Tosun and Lang 2013), similar integration challenges arise in multi-level governance contexts (Briassoulis 2011). A promising way of expanding the framework in this respect is by linking it to the notion of 'functional regulatory spaces,' which span several policy sectors, governance levels, and institutional territories (Varone et al 2013). Regarding the integration of policy outcomes, as Jordan and Lenschow (2010) observe, relatively little research has been conducted on the effects of better integrated policy approaches on actual practices on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the term 'super-wicked' problem has also been developed (c.f. Varone et al 2013;Levin et al 2012;Lazarus 2008), to potentially regain some analytical utility through a narrower focus on additional concerns. The term has particularly been applied to environmental policy or climate change specifically, with Levin et al (2012) explaining how these issues have additional 'wicked' features such as temporal urgency, or solutions required from those causing the problems.…”
mentioning
confidence: 99%
“…The value of these approaches is that governance systems are better equipped to plan for change rather than only what can be predicted [36,37]. In Brazil, the Secretariat of Strategic Affairs for the Presidency conducted a national multi-sectoral scenario study to assess the likely impacts of climate change, and only then identified strategies for adaptation.…”
Section: Externalities and Shared Risks Across Multiple Scalesmentioning
confidence: 99%